Generational Time and Multilinear Form in the Climate Change Novel - Caracciolo, Marco (Cahier voor Literatuurwetenschap, 2024)
Drawing on New Formalism and econarratology, this essay considers the potential of narrative multilinearity in fostering new modes of thinking about generational relations in times of ecological crisis. The starting point is that climate change puts considerable pressure on the forms of generational thinking embedded in Western modernity. The multilinear novels I consider speak to this challenge on a formal level, by revisiting the traditional template of the ‘family saga’, with its multigenerational, temporally distributed structure. The article’s archive includes contemporary novels by James Bradley (Clade), Hanya Yanagihara (To Paradise), and Namwali Serpell (The Old Drift). In different ways and to different degrees, these works reimagine conventionally anthropocentric ideas of generation and kinship, opening them up to entanglements with the nonhuman.